Correlation and Path Coefficient Studies in Sunflower - Buttar, G S; Uppal, H S (Annals of Arid Zone, 2016)
Correlation and relative contribution by different yield attributing characters towards seed yield of sunflower (Helianthus annuus L.) were studied from a field experiment conducted during 1994 and 1995 at PAU, Ludhiana. Seed yield of sunflower showed positive correlation with leaf area index, capitulum weight, 1OOO-grain weight, grains per capitulum, capitulum diameter and root length density during 1994. However, during 1995, positive correlation of seed yield was found with all the above characters except leaf area index. In both the years, highly significant . correlation of seed yield was found with yield attributing characters, viz., capitulum weight, 10OO-grain weight, number of grains per capitulum and capitulum. diameter. Path coefficient analysis revealed that among different characters, contribution of leaf area index was highest (0.1485) during 1994 followed by capitulum diameter (0.0877). During 1995, highest contribution towards seed yield was made by capitulum diameter (0.4255) followed by 1OOO-grain weight (0.0465).